2020
DOI: 10.1002/ejhf.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Omecamtiv mecarbil in chronic heart failure with reduced ejection fraction: GALACTIC‐HF baseline characteristics and comparison with contemporary clinical trials

Abstract: Aims The safety and efficacy of the novel selective cardiac myosin activator, omecamtiv mecarbil, in patients with heart failure with reduced ejection fraction (HFrEF) is being tested in the Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure (GALACTIC‐HF) trial. Here we describe the baseline characteristics of participants in GALACTIC‐HF and how these compare with other contemporary trials. Methods and results Adults with established HFrEF, New York Heart Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 30 publications
8
45
0
1
Order By: Relevance
“…The Chronic Oral Study of Myosin Activation to Increase Contractility in Heart Failure (COSMIC-HF) [ 23 ] was a phase II trial that showed a decrease in NT-pro-BNP levels, heart rate and in ventricular dimensions [ 23 ]. More recently, the Cardiac Myosin Activation with Omecamtiv Mecarbil in Systolic Heart Failure (GALACTIC-HF) trial studied 8256 patients in a randomized fashion to omecamtiv mecarbil or placebo [ 24 ]. There was a nominal (8%) reduction in the composite endpoint of CV death and HF hospitalization, and this effect was formally significant ( p = 0.03).…”
Section: Novel Heart Failure Treatmentsmentioning
confidence: 99%
“…The Chronic Oral Study of Myosin Activation to Increase Contractility in Heart Failure (COSMIC-HF) [ 23 ] was a phase II trial that showed a decrease in NT-pro-BNP levels, heart rate and in ventricular dimensions [ 23 ]. More recently, the Cardiac Myosin Activation with Omecamtiv Mecarbil in Systolic Heart Failure (GALACTIC-HF) trial studied 8256 patients in a randomized fashion to omecamtiv mecarbil or placebo [ 24 ]. There was a nominal (8%) reduction in the composite endpoint of CV death and HF hospitalization, and this effect was formally significant ( p = 0.03).…”
Section: Novel Heart Failure Treatmentsmentioning
confidence: 99%
“…CK-1827452 also known as Omecamtiv mecarbil (INN) accelerates the transition of actin-myosin complex from weakly to strongly bound and increases the number of myosin heads engaged with the thin filament. These effects are independent of calcium transients because CK-1827452-treated cardiomyocytes with isoproterenol augment contraction, whereas β-adrenergic inhibition does not diminish contractility (77) ATOMIC (78). Additional studies indicated that CK-1827452 traps some myosin heads in a weak actin affinity state with slow force development and at high concentrations prolonged cellular relaxation in hiPSC-CMs (79).…”
Section: Known Drugsmentioning
confidence: 99%
“…A randomized, parallel-group, double-blind, phase II conducted over 87 sites in 13 countries (The Chronic Oral Study of Myosin Activation to Increase Contractility in Heart Failure COSMIC-HF trial) showed that CK-1827452 administered to patients with chronic stable symptomatic heart failure increased stroke volume and modestly reduced left ventricular end-diastolic diameter, heart rate, and serum levels of N-terminal brain natriuretic factor, increased systolic ejection time, and it may have improved dyspnea in the high-dose group, though it did not meet the primary endpoint of dyspnea improvement. Many other trails have been conducted and are still under investigation to study this drug (Table 2) (77,78,80).…”
Section: Known Drugsmentioning
confidence: 99%
“…Milestone studies have uncovered the possibility of new treatments for such diseases by demonstrating that small molecules acting as allosteric effectors can modulate the force produced by myosin motors. Three drug candidates acting either as specific inhibitors or activators of cardiac myosin are under phase 3 clinical trials for treatment of distinct heart insufficiencies [60][61][62]. The pockets in which several of these specific allosteric effectors bind have been identified in the myosin molecule (Figure 5).…”
Section: Myosin and Diseasesmentioning
confidence: 99%
“…Des études marquantes ont permis de découvrir la possibilité de nouveaux traitements pour ces maladies en démontrant que de petites molécules agissant comme effecteurs allostériques peuvent moduler la force produite par les moteurs myosine. Trois candidats médicaments agissant soit comme inhibiteurs spécifiques soit comme activateurs de la myosine cardiaque sont en cours d'essais cliniques de phase 3 pour le traitement d'insuffisances cardiaques distinctes [60][61][62]. Les poches dans lesquelles plusieurs de ces effecteurs allostériques spécifiques se lient ont été identifiées dans la molécule de myosine (Figure 5).…”
Section: Myosines Et Maladiesunclassified